Effect of Prophylactic Fibrinogen Concentrate In Scoliosis Surgery (EFISS): a study protocol of two-arm, randomised trial - Martin Repko; Kamil Vrbica; Jan Hudec; Ondrej Hrdy; Michal Galko; Hana Horalkova; Regina Demlova; Michaela Kubelova; Roman Gal (BMJ Open, 2023)
Introduction Fibrinogen is one of the essential coagulation factors. Preoperative lower plasma fibrinogen level has been associated with higher blood loss. Scoliosis surgery presents a challenge for the anaesthetic team, one of the reasons being blood loss and transfusion management. Recently, the prophylactic fibrinogen administration has been a debated topic in various indications. It has been described for example, in urological or cardiovascular surgery, as well as in paediatrics. This pilot study is focused on verifying the feasibility of potential large randomised trial and verifying the safety of prophylactic fibrinogen administration in paediatric scoliosis surgery.Methods and analysis A total of 32 paediatric patients indicated for scoliosis surgery will be recruited. Participants will be randomised into study groups in a 1:1 allocation ratio. Patients in the intervention group will receive prophylactic single dose of fibrinogen, in addition to standard of care. Patients in the control group will receive standard of care without study medication prior to skin incision. The primary aim is to assess the safety of prophylactic fibrinogen administration during scoliosis surgery in children, the incidence of any adverse events (AEs) and reactions will be monitored during participation in the study. The secondary objective is to investigate the additional safety information, feasibility and efficacy of a prophylactic fibrinogen administration. The incidence of AEs and reactions according to selected adverse events of special interest will be monitored. All collected data will be subjected to statistical analysis according to a separate statistical analysis plan.Ethics and dissemination This trial follows the applicable legislation and requirements for good clinical practice according to the International Conference on Harmonisation E6(R2). All essential trial documents were approved by the relevant ethics committee and national regulatory authority (State Institute for Drug Control) and their potential amendments will be submitted for approval.Trial registration number NCT05391412.